Helminth Community Dynamics in Populations of Blue-Winged Teal (Anas discors) Using Two Distinct Migratory Corridors. (1st March 2011) - Garvon, Jason M.; Fedynich, Alan M.; Peterson, Markus J.; Pence, Danny B.
Abstract : The influence of spatially distinct host subpopulations on helminth community structure and pattern was examined in a migratory avian host species. Forty helminth species represented by 24, 082 individuals were collected from 184 blue-winged teal ( Anas discors ; BWT) from 2 primary migratory corridors in Florida (eastern migratory corridor; EMC) and Louisiana and Texas (western migratory corridor; WMC). Mean species richness was greater in BWT from the WMC (x ¯ ± S .E = 10.2   ±   0.3 species) than the EMC (8.6 ± 0.2). The helminth community from the WMC had higher abundances of 6 common/intermediate species. Corridor helminth communities were similar in species composition but less similar when incorporating abundances of those species. Overlapping distributions of phylogenetically related host species that share generalist helminth species across ecologically similar habitats seem to mitigate the isolating mechanisms that are necessary for the distinct coevolutionary pathways to develop between adjacent corridors.